2019
DOI: 10.1017/gmh.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

The integration of idioms of distress into mental health assessments and interventions: a systematic review

Abstract: Background.Psychiatric diagnostic manuals recognise the importance of local expressions of distress in culturally diverse settings [i.e. idioms/cultural concepts of distress (CCDs)], yet there is a lack of consensus on how these should be incorporated into mental health related research.Aims.To perform a narrative synthesis and critical review of research exploring how idioms/CCDs have been integrated into assessment measures and interventions.Method.A systematic review was conducted in accordance with PRISMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 51 publications
0
34
0
2
Order By: Relevance
“…The study demonstrated change in a locally meaningful outcome: “heart–mind problems”. Few prior studies have included locally salient outcomes [ 52 ], which are important to promote engagement, adherence, and scale-up, as well as minimize stigma [ 16 , 53 ]. The intervention and associated implementation materials also underwent a rigorous cultural adaptation process to assure validity of the concepts and strategies for Nepali language and culture [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated change in a locally meaningful outcome: “heart–mind problems”. Few prior studies have included locally salient outcomes [ 52 ], which are important to promote engagement, adherence, and scale-up, as well as minimize stigma [ 16 , 53 ]. The intervention and associated implementation materials also underwent a rigorous cultural adaptation process to assure validity of the concepts and strategies for Nepali language and culture [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For developers that adopt a lexical approach, dictionaries that pay particular attention to culturally different expressions of mental health will be beneficial. Kohrt et al provide a systematic review of transcultural psychiatry and the different cultural idioms of distress that warrant greater attention [ 33 ]. Integrating such vocabulary into the dictionaries of lexical models could mitigate the negative impact of unequal cultural representation in existing psychiatric literature.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Desai and Chaturvedi describe how "idioms of distress" differ between cultural communities and detail how the psychological symptoms in traditional cultures may not fit within existing western psychiatric frameworks [31]. Non-western expressions of mental illness are often not captured in the mental health literature and will therefore be missed by NLP models that are based on our existing medical assessments [31][32][33][34][35][36].…”
Section: Expression Of Datamentioning
confidence: 99%
“…Piloting of the translated items prior to study implementation and qualitative research exploring perceptions of depression and how it relates to interpersonal issues (a domain that was not represented in our reduced scale) and positive affect in this context could also shed light on why items in these two domains performed so poorly and serve as a starting point for generation of a new pool of items to be piloted as part of the scale in this setting. Evidence from other developing countries suggests that the generation of new items with local idioms, either for a new scale or to replace poorly performing items in an existing scale, can generate a more precise measure of depression [43].…”
Section: Public Health Significance and Recommendationsmentioning
confidence: 99%